Infestasi caplak pada ternak kuda di desa Pinabetengan Raya, Kecamatan Tompaso Barat, Kabupaten Minahasa, Provinsi Sulawesi Utara - Ariman, A.P.; Nangoy, M.J.; Tulung, Y.L.R.; Assa, G.V.J. (Universitas Sam Ratulangi, 2021)
This study aims to identify the types of ticks, calculate the prevalence of tick infestations, preferences for body part infestations and preferences for sex infestations in horses in Pinabetengan Raya Village, West Tompaso District, Minahasa Regency, North Sulawesi Province. This research was carried out for one month (thirty days) on 50 horses. Ticks are collected manually using tweezers in sequence starting from the head, neck, back, abdomen, groin, tail and legs. The samples were put in bottles containing 70% alcohol. The results of this study found that the type of tick that infested horse livestock was Boophilus microplus. The prevalence of infestation is 60.78%. The preference based on body part was found to be highest in the neck with an average of 2.82 individual ticks / horses. The average head was 1.75, the back was 0.25, the abdomen was 0.72, the groin was 1.27, the legs were 0.25 and the tail was 0.74 of the individual ticks/horse. Infestation preference based on sex was found to be higher for females (average 10.48 individual ticks / horse) when compared to males (mean 2.64 individual ticks/horse). The type identification found was Boophilus microplus with an infestation prevalence of 62%, with the highest preference on the neck with an average of 2.82% and higher mares with an average of 10.48% individual ticks/horse livestock.Keywords : Ticks Infestation, Prevalence, Preference, Horse